Ecogeographical Characterization of germplasm of tagasaste and escobon (Chamaecytisus Proliferus (L. il.) Link sensulato) from the Canary Islands: soil, climatological and geographical features - Francisco-Ortega, J.=700 1 Jackson, M.T.; Socorro-Monzon, A.R.; Ford-Lloyd, B.V.
(Es, En)
ilus., 28 ref.
Keywords: ECOLOGIA; GEOGRAFIA; GERMOPLASMA; CYTISUS PROLIFERUS; LEGUMINOSAS; ESPAÑA; TAGASASTE; ESCOBON; FORRAJE